Aerobic Oxidation and Oxidative Esterification of 5‐Hydroxymethylfurfural by Gold Nanoparticles Supported on Nanoporous Polymer Host Matrix. Issue 18 (21st August 2018) - Buonerba, Antonio; Impemba, Salvatore; Litta, Antonella Dentoni; Capacchione, Carmine; Milione, Stefano; Grassi, Alfonso
Abstract: The aerobic oxidation and oxidative esterification of 5‐hydroxymethylfurfural (HMF) catalyzed by gold nanoparticles (AuNPs) supported on a semicrystalline nanoporous multiblock copolymer matrix consisting of syndiotactic poly(styrene)‐ cis ‐1, 4‐poly(butadiene) (sPSB) have been investigated. Depending on the reaction parameters (support nanoporosity, presence of water, solvent, temperature, cocatalyst, oxygen pressure), the conversion of HMF can be finely addressed to the formation of the desired oxidation product, such as 2, 5‐diformylfuran (DFF), 5‐formylfuran‐2‐carboxylic acid (FFCA), methyl 5‐(hydroxymethyl)furan‐2‐carboxylate (MHMFC), dimethyl furan‐2, 5‐dicarboxylate (DMFC), and furan‐2, 5‐dicarboxylic acid (FDCA), under optimized reaction conditions. The AuNP–sPSB catalyst is highly effective and selective because the polymer support acts as a conveyor and concentrator of the reactants toward the catalytic sites. Abstract : Host with the most ! The aerobic oxidation and oxidative esterification of 5‐hydroxymethylfurfural, catalyzed by gold nanoparticles supported on a semicrystalline nanoporous polymer matrix, have been investigated. The selectively permeable support allows fine regulation of the environment surrounding the catalytic sites, which results in fine control of the oxidation process.